2022
DOI: 10.25248/reas.e10686.2022
|View full text |Cite
|
Sign up to set email alerts
|

Stress associated to geographic tongue transformation from passive to active during the Covid-19 pandemic: case report

Abstract: Objective: Report a case of passive geographic tongue that became active due to the presence of severe stress associated to the coronavirus disease 2019 (COVID-19) pandemic. Case details: In January 2019, a 42-years-old Caucasian female was included in a survey on geographic tongue (GT). At that time, although she reported having the condition, on intraoral examination, no atrophic areas or whitish margins were observed on her tongue (classic clinical signs of GT). In November 2020, she was contacted again and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
(6 reference statements)
1
2
0
Order By: Relevance
“…Recent studies have demonstrated the association of GT to the presence of anxiety, stress, and depression [ 20 , 38 ], corroborating the results of this study, where stress was statistically related to the worsening of the symptoms of geographic tongue. Furthermore, it was observed that younger patients were more susceptible to stress and, consequently, developed exacerbation or worsening of their symptoms.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Recent studies have demonstrated the association of GT to the presence of anxiety, stress, and depression [ 20 , 38 ], corroborating the results of this study, where stress was statistically related to the worsening of the symptoms of geographic tongue. Furthermore, it was observed that younger patients were more susceptible to stress and, consequently, developed exacerbation or worsening of their symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…It continues to be doubtful whether or not signs and symptoms are manifestations of the disease or arise because of the lack of immune response [ 47 ]. The oral manifestations associated with COVID-19 are real, therefore the intraoral examination is important to be performed in all patients with COVID-19 [ 38 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation